2017
DOI: 10.1155/2017/7120962
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk between ROS and Autophagy in the Field of Transplantation Medicine

Abstract: Many factors during the transplantation process influence posttransplant graft function and survival, including donor type and age, graft preservation methods (cold storage, machine perfusion), and ischemia-reperfusion injury. Successively, they will lead to cellular and molecular alterations that determine cell and ultimately organ fate. Oxidative stress and autophagy are implicated in posttransplant outcome since they are both affected by the stress responses triggered in each step (donor, preservation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 119 publications
4
32
0
Order By: Relevance
“…37 Additionally, it is known that ROS production induced by mitochondrial dysfunction leads to structural and functional cell damages. 38 Two distinct phases of cold ischaemia were observed up until 6 hours in this study, and our results confirm observations in several other organs, such as the liver and kidney. [39][40][41] We confirmed that beyond 6 hours, islets started to lose function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…37 Additionally, it is known that ROS production induced by mitochondrial dysfunction leads to structural and functional cell damages. 38 Two distinct phases of cold ischaemia were observed up until 6 hours in this study, and our results confirm observations in several other organs, such as the liver and kidney. [39][40][41] We confirmed that beyond 6 hours, islets started to lose function.…”
Section: Discussionsupporting
confidence: 91%
“…After 6 hours, a further decrease in ATP concomitant with a xanthine/hypoxanthine increase revealed that cells are unable to cope with a longer ischaemia time . Additionally, it is known that ROS production induced by mitochondrial dysfunction leads to structural and functional cell damages . Two distinct phases of cold ischaemia were observed up until 6 hours in this study, and our results confirm observations in several other organs, such as the liver and kidney .…”
Section: Discussionsupporting
confidence: 85%
“…Autophagy is an evolutionarily conserved and lysosome‐dependent system which functions in the degradation and recycling of proteins, organelles, and other cellular components . The current thinking by some scholars is that autophagy needs to stay at a safe level in the process of liver preservation in order to play a protective role in liver transplantation . Both autophagy caused by excessive damage and insufficient autophagy will prompt liver apoptosis and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…With the DCD liver in a hypothermic environment, HOPE relieves ischemic injury by providing sufficient energy and oxygen and delivers metabolic substrates to the overall vasculature of DCD liver for recovering ATP level, such as histidine, tryptophan, and acetone dicarboxylic acid in HTK or adenine and ribose in Belzer MPS . The generation and restoration of ATP is precondition for autophagy activation which prompt the elimination of damaged organelles and ROS by chaperone‐mediated autophagy pathway P62 delivery pathway, and mitophagy pathway . In addition, autophagy activation provides more energy to damaged cells to prevent apoptosis and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…All of these data indicate that autophagy is implicated in the pathogenesis of obesity through the regulation of adipogenic differentiation. Additionally, there is a growing consensus that ROS generated in oxidative stress acts as an early inducer of autophagy [31,32]. H 2 O 2 is proposed to initiate autophagy directly via the regulation of AMP-activated protein kinase (AMPK).…”
Section: Discussionmentioning
confidence: 99%